Limits for the Content of Heavy Metals and Arsenic as a Means of Ensuring Safe Use of Herbal Medicinal Products - M. S. Galenko; I. V. Gravel; N. Yu. Velts; R. N. Alyautdin (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2021)
Herbal medicinal products (HMPs) are widely used in medical practice due to their availability, ease of use, and relatively safe pharmacological proﬁle. However, medicinal plants are capable of accumulating heavy metals and arsenic which can have toxic eﬀect on the human body when found in HMPs. The aim of the study was to summarise and analyse requirements of the Russian and foreign pharmacopoeias for the limits of heavy metals and arsenic in HMPs. National and regional pharmacopoeias have limits for the content of the major toxic elements (lead, cadmium, mercury, chromium, and arsenic) in HMPs. The study showed that the Indian and Japanese pharmacopoeias include only semi-quantitative methods for determination of heavy metals and arsenic, while the Russian and Chinese pharmacopoeias allow for the use of both quantitative and semi-quantitative methods. It was demonstrated that the limits for heavy metals and arsenic are the same for herbal substances and HMPs. The development of consistent approaches to determination of heavy metals and arsenic content, a systematic transition to quantitative methods of analysis, and establishment of individual limits for toxic elements in diﬀerent HMP dosage forms, will make it possible to achieve the so-called consistent harmonisation, ensure reliable assessment of the content of heavy metals and arsenic, and minimize the risk of their entering human body with HMPs.